5y-2=-14-3y

Simple and best practice solution for 5y-2=-14-3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y-2=-14-3y equation:


Simplifying
5y + -2 = -14 + -3y

Reorder the terms:
-2 + 5y = -14 + -3y

Solving
-2 + 5y = -14 + -3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3y' to each side of the equation.
-2 + 5y + 3y = -14 + -3y + 3y

Combine like terms: 5y + 3y = 8y
-2 + 8y = -14 + -3y + 3y

Combine like terms: -3y + 3y = 0
-2 + 8y = -14 + 0
-2 + 8y = -14

Add '2' to each side of the equation.
-2 + 2 + 8y = -14 + 2

Combine like terms: -2 + 2 = 0
0 + 8y = -14 + 2
8y = -14 + 2

Combine like terms: -14 + 2 = -12
8y = -12

Divide each side by '8'.
y = -1.5

Simplifying
y = -1.5

See similar equations:

| 18x-12= | | -7(z+5)=-8z | | k-17=(-12) | | -41=6x+7(x-17) | | 5+4x-16=9 | | -w+9=-31 | | 2.5x=5x-3-x | | a+3=12-10 | | 7x+5(x-12)=12 | | f(x)=-6x^5+9x^4-12x^3-15 | | (19x-7)+(6x-12)= | | 3(x+4)=4(3+21) | | -4=0.5p-7 | | 6y+2-y=6+4y-10 | | 3x+7x-30=12+50+20x | | h(x)=16x^2+65x+5 | | ln(11X-3)=0 | | 2x+5=6x+8 | | 35-37=8 | | 3.8n-13=1.4n+15 | | b-12=-16 | | -9x+24=80-2 | | 12a-4b-15a+b= | | 7+2[n-5]n=3.6 | | 9ac+6a= | | g+-2.5+7=4 | | f(x)=x+8ln(3x) | | b^2-b-20=20 | | -7n=70 | | 5xy^2-3x+2y^2+7x+13xy^2= | | 97-9x=-47 | | 10x^2+6x=4 |

Equations solver categories